2011 IEEE International Conference on Systems, Man, and Cybernetics 2011
DOI: 10.1109/icsmc.2011.6084201
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Sensor Network algorithm for predicting the spatiotemporal evolution of hazardous phenomena

Abstract: We present a novel decentralized Wireless Sensor Network (WSN) algorithm which can estimate both the speed and direction of an evolving diffusive hazardous phenomenon (e.g. a wildfire, oil spill, etc.). In the proposed scheme we approximate a progressing hazard's front as a set of line segments. The spatiotemporal evolution of each line segment is modeled by a modified 2D Gaussian function. As the phenomenon evolves, the parameters of this model are updated based on the analytical solution of a Kullback-Leible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Then, by applying the resulting mixture weight values into (11) and (12) the Master calculates the parameters (û i and s i ) of the Normal distribution that best approximates the Gaussian mixture. Finally, having available these parameters (û i andŝ i ), along with the prior model parameters (u i , and s i ), S M i applies them to equation (13) to obtain parameters (u * i , s * 2 i ) of the posterior speed model.…”
Section: Model Updatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, by applying the resulting mixture weight values into (11) and (12) the Master calculates the parameters (û i and s i ) of the Normal distribution that best approximates the Gaussian mixture. Finally, having available these parameters (û i andŝ i ), along with the prior model parameters (u i , and s i ), S M i applies them to equation (13) to obtain parameters (u * i , s * 2 i ) of the posterior speed model.…”
Section: Model Updatingmentioning
confidence: 99%
“…Each segment of this curve (to be called the local front) can be adequately characterized by a small set of parameters, namely an orientation angle and the direction and speed of the segment's propagation. In [13], [14] we have shown that the spatiotemporal evolution of each local front can be modeled by a modified 2D Gaussian function and that it is possible to track the front by updating the model parameters using a distributed processing scheme which solves a Kullback-Leibler divergence minimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…To address these severe limitations we have introduced in [12,13] a distributed approach which is based on probabilistic modeling and can continuously estimate, with high accuracy, the space-and time-varying evolution characteristics (direction and speed) of a progressing hazard using low density WSNs. As for all WSN schemes, computer simulations can be used to assess the expected estimation accuracy as a function of the network's density.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge our proposed emulation scheme is the first attempt to use a small number of sensor nodes to realistically estimate the energy consumption of a collaborative algorithm in a large-scale WSN implementation. We demonstrate its capabilities using the distributed algorithm we introduced in [12,13] for estimating the spatiotemporal evolution parameters of diffusing environmental hazards. WSN emulation provides convincing evidence that the collaborative algorithm is suitable for large-scale WSN deployment since it respects the memory, processing and energy constraints of commodity sensor nodes used in WSN implementations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation